The Influence of Digital Marketing, Online Customer Review, and Trust on Customer Decisions to Save in Islamic Banks with Savings Inclination as a Mediating Variable (A Study on Customers of Bank Syariah Indonesia in Malang City) - Moh. Rizky Abdillah; Irmayanti Hasan (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
The goal of this study is to examine how Digital Marketing (X1), Online Customer Review (X2), and Trust (X3) impact Customer Decisions to save in Islamic banks (Y), with Savings Inclination acting as a mediator (Z). The research will specifically look at customers of Bank Syariah Indonesia (BSI) in Malang City. This study is motivated by the rapid advancements in digital technology, which have a growing impact on customer behavior when it comes to financial choices, especially in the realm of Islamic banking. This study utilises a quantitative method with an associative research design. Data was gathered by distributing questionnaires to 110 BSI Mobile users in five districts of Malang City. The data was analysed using Partial Least Square (PLS). The results show that Digital Marketing (X1), Online Customer Review (X2), and Trust (X3) have a significant impact on both Savings Inclination (Z) and Customer Decisions (Y). Additionally, Savings Inclination (Z) acts as a mediator in the relationship between the three independent variables and Customer Decisions (Y). These findings are anticipated to aid in the improvement of Digital Marketing strategies in Islamic banking and bolster customer confidence in Sharia-compliant banking services.